Perspectives for Buck Kids in Dairy Goat Farming - Meijer, Ellen; Goerlich, Vivian C.; Brom, René van den; Giersberg, Mona F.; Arndt, Saskia S.; Rodenburg, T. Bas (Frontiers in Veterinary Science, 2021)
To start milk production, dairy goats need to give birth at least once. While most female kids are reared to become the next generation of dairy goats, only a small proportion of male kids (buck kids) are reared with reproduction aims. The market for buck kid meat, especially within Northern European countries, is currently relatively small compared to the number of bucks born. Therefore, the purposes for buck kids are limited and a substantial proportion of buck kid meat is used for pet food. Due to the limited economic value of buck kids, farmers are faced with a dilemma. Although raising bucks costs more money than it yields, the birth of kids is a prerequisite for production of milk and should be seen as an investment for business-wise healthy dairy goat farming. In that perspective, dairy goat farmers have an ethical responsibility towards buck kids, as well. In this paper, we compare various scenarios of dealing with the issue of surplus male animals. We provide recommendations for the rearing of buck kids based on the sector`s experience and current practice in the Netherlands. Reducing the number of surplus (male) offspring, e.g., by an optimized prolonged lactation management and/or by artificial insemination with sex-sorted semen, could alleviate the issue of low value buck kids. Killing surplus animals before or directly after birth, on the other hand, is met with increasing societal scrutiny. Initiatives to propagate a market for buck kid meat for human consumption are important to enable a suitable and sustainable production system. To maintain the health and welfare of goat kids, amongst other factors, sufficient and good quality colostrum, milk, and an appropriate diet as they grow older, needs to be provided. One option to assure the safeguarding of health and welfare of all goat kids are quality assurance schemes for milk production. These schemes make dairy farmers accountable for the health and welfare of all kids. We conclude that the combination of reducing the number of surplus kids, increasing the demand for goat products, and quality assurance schemes that may help to safeguard the welfare of buck kids.